PENGARUH PELAYANAN, PROMOSI DAN FASILITAS TERHADAP MINAT BELI PADA PT. ADULAM NAMORA WISATA TOUR &TRAVEL - MARIANAWATI SIREGAR; HERYENZUS . (LP2MTBM MAKARIOZ, 2020)
Developments in the business world in the current era of economic globalization, have triggered a fairly tight competitionbetween companies engaged in services, with the existence of these conditions companies are required to be more carefulin determining their competitive strategy. In this regard the research aims to test and find out how important the influence ofservices, promotions, and facilities on buying interest in PT Adulam Namora Wisata Tour & Travel. This research is aquantitative study using descriptive methods and using multiple linear analysis. The sampling technique uses probabilitysampling, with simple random sampling. In this study the number of samples taken was 298 people. Where is the datacollection method by distributing questionnaires to respondents to fill out. The results of simultaneous research note thatthere is a significant influence between service, promotion and facility variables on buying interest at PT Adulam NamoraWisata Tour & Travel. This is reinforced by the acquisition of the calculated F value of 182.170 is greater than the value of ttable 2.64. While the results of the study are known to have a significant influence between the independent variables withthe dependent variable. This is based on the results of the t test of service, promotion, and facility variables all of which havevalues below 0.05, so H0 is rejected and H1 is accepted. Adjusted R Square value proves that 65.0 percent of buyinginterest can be explained by the three independent variables, while the remaining 35.0 percent is explained by othervariables outside the three variables used in this study.